A Review of the Pathogenesis of Corneal Vascularization - Jantzi, J.D (Canadian Journal of Optometry, 2021)
Corneal vascularization is a subject of importance not only to research scientists but also to optometrists who in daily clinical practice are responsible for monitoring the ocular health of their patients. Contact lens patients in particular must be examined regularly and on a continuing basis for signs of pathological corneal changes such as vascularization which indicate an intolerance to their contact lenses. The purpose of this paper is to review what is presently known about the pathogenesis of corneal vascularization since an understanding of this condition may give us insight as to why it occurs in certain patients; for example contact lens wearers.